PENGELOLAAN SUNGAI MENURUT PERATURAN DAERAH KOTA BANJARMASIN N0 2 TAHUN 2007 - Faris Ali Sidqi (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
In order to maintain the function of the river is necessary legal instrumentwhich is able to maintain preservation of the river, especially the environmentalaspects that the provisions of these regulations can be accepted by the public inaccordance with the evolving culture. This study aimed to describe the regulationconcerning the management of rivers according to Regional Regulation (Perda)No. Banjarmasin 2 Year 2007 as well as sanctions for violations. The study usedliterature such as books, legislation, print and electronic media, as well as otherdocuments relating to the cases studies. The writing is done in the form ofqualitative descriptive